Peningkatan Kemampuan Guru Kimia Dalam Mengidentifikasi Sain Ilmiah dari Budaya Masyarakat Sasak, Samawa dan Mbojo (Etnosasambo) - Muntari; Andayani, Yayuk; Purwoko, Agus Abhi; Haris, Mukhtar; Adiguna, Sya’ban Putra; Lestari, Eka Netia; Hurairah, Baiq Endah (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
The ability of chemistry teachers to identify scientific science contained in the culture of the Sasak, Samawa and Mbojo (Ethnosasambo) peoples varies. Most teachers find it difficult to connect science concepts with existing cultures, so socialization and training activities are carried out which aim to improve teachers' ability to identify science concepts in ethnosasambo. The socialization activity was attended by 30 teachers from 10 high schools and vocational schools in West Lombok Regency. Data on teacher ability before and after socialization activities were measured using evaluation questionnaires, and the results were analyzed and described to describe changes in teacher abilities after the activity. The results show that teachers' ability to identify the concept of science in ethnosasambo is increasing. It is hoped that this good experience motivates teachers to integrate ethnosasambo culture into learning activities so that classroom learning becomes more meaningful.